Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

Remote sensing-based evapotranspiration and soil water balance estimation for a tropical pasture in Brazil using the SETMI model - Vitor de J. M. Bianchini; Ivo Z. Gonçalves; Christopher M. U. Neale; Alex da S. Sechi; Thieres G. F. da Silva; Fábio R. Marin (International Journal of Biometeorology, 2026)
Developing strategies to improve pasture yield and mitigate environmental impacts is crucial in Southeastern Brazil, where livestock farming faces competition for areas with profitable crops. Accurate evapotranspiration (ET) estimation is an essential component of managing soil water balance and evaluating pasture response to drought and water productivity. The objectives of this study were to: (1) develop a relationship between the basal crop coefficient (K cb ) derived from observed ET, and the soil-adjusted vegetation index (SAVI) from PlanetScope images; (2) integrate the K cb -SAVI relationship into remote sensing-based soil water balance (RSWB) to generate daily K cb and then simulate the actual evapotranspiration (ET a ) of an intensively grazed tropical pasture in the state of São Paulo, Brazil; and (3) use the spatialized estimate of ET a to assess the crop water productivity ( $${\text{W}\text{P}}_{{\text{E}\text{T}}_{\text{a} \text{m}\text{o}\text{d}}}$$ ). The K cb -SAVI relationship developed in this study showed a strong positive correlation between SAVI and K cb , with Pearson correlation coefficient ( $$ρ$$ ) and $${\text{R}}^{2}$$ values of 0.89 and 0.79, respectively. Comparisons between observed and simulated ET a indicated good agreement for daily values ( $$\text{R}\text{M}\text{S}\text{E}$$ of 0.59 mm d −1 , Willmott index of agreement ( $$\text{D}$$ ) of 0.86) and for average weekly values ( $$\text{R}\text{M}\text{S}\text{E}$$ of 0.38 mm d −1 , $$\text{D}$$ of 0.93). Biases of -5% and 3% were obtained for modelled cumulative ET a in the years 2021–2022 and 2022–2023, respectively. The average $${\text{W}\text{P}}_{{\text{E}\text{T}}_{\text{a} \text{m}\text{o}\text{d}}}$$ values were similar for both years, 2.2 kg m −3 in 2021–2022 and 1.8 kg m −3 in 2022–2023. These findings demonstrate the potential of RSWB, ET a , and WP assessments to enhance decision-making, monitoring, and management of water resources in pasture-based livestock farming.

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Genomic Variation in Vitis Vinifera, from Extant to Contemporary Varieties - Zeki Kaya; Funda Özdemir Değirmenci; Sevgi Yorulmaz; Kıvılcım B. Vural; Christina Luke; Christopher H. Roosevelt; Mehmet Somel; David B. Neale (Plant Molecular Biology Reporter, 2025)

How can Future Climate Change Affect the Corn Production System in Nebraska, USA? - Ivo Z. Gonçalves; Izael M. Fattori; Christopher M. U. Neale; Carlos A. C. Santos; Alex Ruane; Meridel M. Phillips; Fábio R. Marin (International Journal of Plant Production, 2024)

High-throughput physiological phenotyping of crop evapotranspiration at the plot scale - Geng (Frank) Bai; Burdette Barker; David Scoby; Suat Irmak; Joe D. Luck; Christopher M.U. Neale; James C. Schnable; Tala Awada; William P. Kustas; Yufeng Ge (Field Crops Research, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Toward automated irrigation management with integrated crop water stress index and spatial soil water balance - Sandeep Bhatti; Derek M. Heeren; Susan A. O’Shaughnessy; Christopher M. U. Neale; Jacob LaRue; Steve Melvin; Eric Wilkening; Geng Bai (Precision Agriculture, 2023)
Decision support systems intended for precision irrigation aim at reducing irrigation applications while optimizing crop yield to achieve maximum crop water productivity (CWP). These systems incorporate on-site sensor data, remote sensing inputs, and advanced algorithms with spatial and temporal characteristics to compute precise crop water needs. The availability of variable rate irrigation (VRI) systems enables irrigation applications at a sub-field scale. The combination of an appropriate VRI system along with a precise decision support system would be ideal for improved CWP. The objective of this study was to compare and evaluate two decision support systems in terms of seasonal applied irrigation, crop yield, and CWP. This study implemented the Spatial EvapoTranspiration Modeling Interface (SETMI) model and the Irrigation Scheduling Supervisory Control and Data Acquisition (ISSCADA) system for management of a center pivot irrigation system in a 58-ha maize-soybean field during the 2020 and 2021 growing seasons. The irrigation scheduling methods included: ISSCADA plant feedback, ISSCADA hybrid, common practice, and SETMI. These methods were applied at irrigation levels of 0, 50, 100, and 150% of the full irrigation prescribed by the respective irrigation scheduling method. Data from infrared thermometers (IRTs), soil water sensors, weather stations, and satellites were used in the irrigation methods. Mean seasonal irrigation prescribed was different among the irrigation levels and methods for the 2 years. The ISSCADA plant feedback prescribed the least irrigation among the methods for majority of the cases. The common practice prescribed the largest seasonal irrigation depth among the methods for three crop-year cases. The maize yield in rainfed was found to be significantly lower than the irrigated levels in 2020 since 2020 was a dry year. No significant differences were observed in crop yield among the different irrigation methods for both years. The CWP among the different irrigation methods ranged between 2.72 and 3.15 kg m −3 for 2020 maize, 1.03 and 1.13 kg m −3 for 2020 soybean, 3.57 and 4.24 kg m −3 for 2021 maize, and 1.19 and 1.48 kg m −3 for 2021 soybean. Deficit level (50%) had the largest irrigation water productivity in all crop-year cases in this study. The ISSCADA and SETMI systems were found to reduce irrigation applications as compared to the common practice while maintaining crop yield. This study was the first to implement the newly developed integrated crop water stress index (iCWSI) thresholds and the ISSCADA system for site-specific irrigation of maize and soybean in Nebraska.

Evapotranspiration adjustment for irrigated maize–soybean rotation systems in Nebraska, USA - Ivo Z. Gonçalves; Christopher M. U. Neale; Andy Suyker; Fábio R. Marin (International Journal of Biometeorology, 2023)

Enhancing predictive ability of optimized group method of data handling (GMDH) method for wildfire susceptibility mapping - Trang Thi Kieu Tran; Sayed M. Bateni; Fatemeh Rezaie; Mahdi Panahi; Changhyun Jun; Clay Trauernicht; Christopher M.U. Neale (Agricultural and Forest Meteorology, 2023)

Heat acclimation reduces the effects of whole-body hyperthermia on knee-extensor relaxation rate, but does not affect voluntary torque production - Ralph Joseph Frederick Hills Gordon; Jodie Natasha Moss; Federico Castelli; Thomas Reeve; Ceri Elen Diss; Christopher James Tyler; Neale Anthony Tillin (European Journal of Applied Physiology, 2023)
Purpose This study investigated the effects of acute hyperthermia and heat acclimation (HA) on maximal and rapid voluntary torque production, and their neuromuscular determinants. Methods Ten participants completed 10 days of isothermic HA (50 °C, 50% rh) and had their knee-extensor neuromuscular function assessed in normothermic and hyperthermic conditions, pre-, after 5 and after 10 days of HA. Electrically evoked twitch and octet (300 Hz) contractions were delivered at rest. Maximum voluntary torque (MVT), surface electromyography (EMG) normalised to maximal M-wave, and voluntary activation (VA) were assessed during brief maximal isometric voluntary contractions. Rate of torque development (RTD) and normalised EMG were measured during rapid voluntary contractions. Results Acute hyperthermia reduced neural drive (EMG at MVT and during rapid voluntary contractions; P < 0.05), increased evoked torques ( P < 0.05), and shortened contraction and relaxation rates ( P < 0.05). HA lowered resting rectal temperature and heart rate after 10 days ( P < 0.05), and increased sweating rate after 5 and 10 days ( P < 0.05), no differences were observed between 5 and 10 days. The hyperthermia-induced reduction in twitch half-relaxation was attenuated after 5 and 10 days of HA, but there were no other effects on neuromuscular function either in normothermic or hyperthermic conditions. Conclusion HA-induced favourable adaptations to the heat after 5 and 10 days of exposure, but there was no measurable benefit on voluntary neuromuscular function in normothermic or hyperthermic conditions. HA did reduce the hyperthermic-induced reduction in twitch half-relaxation time, which may benefit twitch force summation and thus help preserve voluntary torque in hot environmental conditions.

Hybrid-based approaches for the flood susceptibility prediction of Kermanshah province, Iran - Sina Paryani; Mojgan Bordbar; Changhyun Jun; Mahdi Panahi; Sayed M. Bateni; Christopher M. U. Neale; Hamidreza Moeini; Saro Lee (Natural Hazards, 2023)

Estimation of daily reference evapotranspiration from limited climatic variables in coastal regions - Hamidreza Vosoughifar; Helaleh Khoshkam; Sayed M. Bateni; Changhyun Jun; Tongren Xu; Shahab S. Band; Christopher M. U. Neale (Hydrological Sciences Journal, 2023)

Novel hybrid models by coupling support vector regression (SVR) with meta-heuristic algorithms (WOA and GWO) for flood susceptibility mapping - Fatemeh Rezaie; Mahdi Panahi; Sayed M. Bateni; Changhyun Jun; Christopher M. U. Neale; Saro Lee (Natural Hazards, 2022)

Trends of extreme air temperature and precipitation and their impact on corn and soybean yields in Nebraska, USA - Carlos A. C. dos Santos; Christopher M. U. Neale; Mesfin M. Mekonnen; Ivo Zution Gonçalves; Gabriel de Oliveira; Osias Ruiz-Alvarez; Babak Safa; Clinton M. Rowe (Theoretical and Applied Climatology, 2022)

Characterization of Concussive Events in Professional American Football Using Videogrammetry - Ann M. Bailey; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Neal Carter; David Hessel; Stephen Beier; William Neale (Annals of Biomedical Engineering, 2020)

Calibration of a common shortwave multispectral camera system for quantitative agricultural applications - J. Burdette Barker; Wayne E. Woldt; Brian D. Wardlow; Christopher M. U. Neale; Mitchell S. Maguire; Bryan C. Leavitt; Derek M. Heeren (Precision Agriculture, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Water availability drives signatures of local adaptation in whitebark pine ( Pinus albicaulis Engelm.) across fine spatial scales of the Lake Tahoe Basin, USA - Brandon M. Lind; Christopher J. Friedline; Jill L. Wegrzyn; Patricia E. Maloney; Detlev R. Vogler; David B. Neale; Andrew J. Eckert (Molecular Ecology, 2017)
Patterns of local adaptation at fine spatial scales are central to understanding how evolution proceeds, and are essential to the effective management of economically and ecologically important forest tree species. Here, we employ single and multilocus analyses of genetic data ( n = 116 231 SNP s) to describe signatures of fine‐scale adaptation within eight whitebark pine ( Pinus albicaulis Engelm.) populations across the local extent of the environmentally heterogeneous Lake Tahoe Basin, USA . We show that despite highly shared genetic variation ( F ST = 0.0069), there is strong evidence for adaptation to the rain shadow experienced across the eastern Sierra Nevada. Specifically, we build upon evidence from a common garden study and find that allele frequencies of loci associated with four phenotypes (mean = 236 SNP s), 18 environmental variables (mean = 99 SNP s), and those detected through genetic differentiation ( n = 110 SNP s) exhibit significantly higher signals of selection (covariance of allele frequencies) than could be expected to arise, given the data. We also provide evidence that this covariance tracks environmental measures related to soil water availability through subtle allele frequency shifts across populations. Our results replicate empirical support for theoretical expectations of local adaptation for populations exhibiting strong gene flow and high selective pressures and suggest that ongoing adaptation of many P. albicaulis populations within the Lake Tahoe Basin will not be constrained by the lack of genetic variation. Even so, some populations exhibit low levels of heritability for the traits presumed to be related to fitness. These instances could be used to prioritize management to maintain adaptive potential. Overall, we suggest that established practices regarding whitebark pine conservation be maintained, with the additional context of fine‐scale adaptation.

Distribution and Drivers of a Widespread, Invasive Wetland Grass, Phragmites australis, in Wetlands of the Great Salt Lake, Utah, USA - A. Lexine Long; Karin M. Kettenring; Charles P. Hawkins; Christopher M. U. Neale (Wetlands, 2017)

Modeling delivery performance in pressurized irrigation systems from simulated peak-demand flow configurations - Daniele Zaccaria; Christopher M. U. Neale (Irrigation Science, 2014)

Simulation of peak-demand hydrographs in pressurized irrigation delivery systems using a deterministic–stochastic combined model. Part II: model applications - Daniele Zaccaria; Nicola Lamaddalena; Christopher M. U. Neale; Gary P. Merkley (Irrigation Science, 2013)

Simulation of peak-demand hydrographs in pressurized irrigation delivery systems using a deterministic–stochastic combined model. Part I: model development - Daniele Zaccaria; Nicola Lamaddalena; Christopher M. U. Neale; Gary P. Merkley; Nicola Palmisano; Giuseppe Passarella (Irrigation Science, 2013)

Fusion of remotely sensed data for soil moisture estimation using relevance vector and support vector machines - Bushra Zaman; Mac McKee; Christopher M. U. Neale (International Journal of Remote Sensing, 2012)

Trends in indices for extremes in daily temperature and precipitation over Utah, USA - Carlos A. C. dos Santos; Christopher M. U. Neale; Tantravahi V. R. Rao; Bernardo B. da Silva (International Journal of Climatology, 2011)
The main objective of this study was to analyse the trends in 20 annual extreme indices of temperature and precipitation for Utah, USA. The analyses were conducted for 28 meteorological stations, during the period from 1930 to 2006, characterized by a long‐term and high‐quality dataset. The software used to process the data was the RClimdex 1.0. The analyses of extreme temperature indices have identified an increase in air temperature in Utah during the last century. Meanwhile, the analyses of precipitation indices showed a large variation throughout the studied area and time period, and, in general, with few statistically significant trends. Thus, it was not possible to conclude that significant changes in precipitation have occurred in this region over the last century. Copyright © 2010 Royal Meteorological Society

High-resolution mapping of river-hydrothermal water mixing: Yellowstone National Park - M. Bayani Cardenas; Christopher M.U. Neale; Cheryl Jaworowski; Henry Heasler (International Journal of Remote Sensing, 2011)

Flexible delivery schedules to improve farm irrigation and reduce pressure on groundwater: a case study in southern Italy - Daniele Zaccaria; Ines Oueslati; Christopher M. U. Neale; Nicola Lamaddalena; Michele Vurro; Luis S. Pereira (Irrigation Science, 2010)

Ganoderma and Amauroderma species associated with root-rot disease of Acacia mangium plantation trees in Indonesia and Malaysia - Morag Glen; Neale L. Bougher; Anthony A. Francis; Susan Q. Nigg; Su See Lee; Ragil Irianto; Karen M. Barry; Christopher L. Beadle; Caroline L. Mohammed (Australasian Plant Pathology, 2009)

Daily evapotranspiration estimates from extrapolating instantaneous airborne remote sensing ET values - José L. Chávez; Christopher M. U. Neale; John H. Prueger; William P. Kustas (Irrigation Science, 2008)

Tidal marshes as a source of optically and chemically distinctive colored dissolved organic matter in the Chesapeake Bay - Maria Tzortziou; Patrick J. Neale; Christopher L. Osburn; J. Patrick Megonigal; Nagamitsu Maie; Rudolf JaffÉ (Limnology and Oceanography, 2008)
The role of tidal marshes as a source of dissolved organic carbon (DOC) and colored dissolved organic matter (CDOM) for adjacent estuarine waters was studied in the Rhode River subestuary of the Chesapeake Bay. Water in a tidal creek draining brackish, high‐elevation marshes was sampled every hour during several semidiurnal tidal cycles in order to examine the tidal exchange of dissolved organic matter (DOM). Water leaving the marsh during ebbing tide was consistently enriched in DOC compared to water entering the marsh during flooding tide. There was a net DOC export from the marsh to the estuary during seasons of both low and high marsh plant biomass. Optical analysis demonstrated that, in addition to contributing to the carbon budgets, the marsh had a strong influence on the estuary’s CDOM dynamics. Marsh‐exported CDOM had optical properties that were consistently and markedly different from those of CDOM in the adjacent estuary. Specifically, marsh CDOM had: (1) considerably stronger absorption, (2) larger DOC‐specific absorption, (3) lower exponential spectral slope, (4) larger fluorescence signal, (5) lower fluorescence per unit absorbance, and (6) higher fluorescence at wavelengths >400 nm. These optical characteristics are indicative of relatively complex, high‐molecular‐weight, aromatic‐rich DOM, and this was confirmed by results of molecular‐weight‐distribution analysis. Our findings illustrate the importance of tidal marshes as sources of optically and chemically distinctive dissolved organic compounds, and their influence on CDOM dynamics, DOC budgets, and, thus, photochemical and biogeochemical processes, in adjacent estuarine ecosystems.